PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN PEMBAYARAN PAJAK DAN PERSEPSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Pada KPP Pratama Kisaran) - Pardede, Sovia Lolita; Setiadi, Aulia Trisna; Wongsosudono, Corinna (JURNAL MUTIARA AKUNTANSI, 2020)
The goal of this research is to analyze the effect of tax knowledge, tax payments awareness, and tax perceptions on taxpayer compliance at Kantor Pelayanan Pajak Pratama Kisaran. This research used quantitative research methods. The population of this research were taxpayers registered at Kantor Pelayanan Pajak Pratama Kisaran, 1933 taxpayers and as many as 95 research samples. Data collection techniques using questionnaires that are distributed directly to 95 taxpayers.The results of 95 respondent, showed that tax knowledge, tax payment awareness and tax perceptionsilmutaneously affect to taxpayer compliance. The result of calculation has been done is obtained sig value of 0,00<0,05 so the hypothesis is accepted. Partially tax knowledge has no effect on taxpayer compliance with a sig value 0,990 >0,05 ,then the hypothesis is rejected. While tax payment awareness and tax perpections affect taxpayer compliance, by sig value tax payment awareness of 0,011 <0,05 so the hypothesis is accepted and tax perpections of 0,002 <0,05 so the hypothesis is accepted.